Identification of Gall Stones through Ultrasonography in Asymptomatic Patients - Imran Khan Memon, Bhagwan Das, Kailash Kumar Daseja, Inayatullah, Muhammad Rashid Rasul, Akhtar Hussain Phul (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To identify gall stones through ultrasonography in asymptomatic patients. Study Design: Prospective study Place and Duration of Study: Department of Radiology, Chandka Medical College Hospital, Larkana from 1st January 2021 to 31st December 2021. Methodology: Two hundred and fifty patients who were not having symptoms of gallbladder stones and were diagnosed through ultrasonography were enrolled. The examination was recommended post 8 hour fasting period. The stones which were stuck in neck of gallbladder or main gallbladder were also observed and their dimensional measurements were taken. The inflammation of the gallbladder was analyzed through the gallbladder thickness. All the demographic variables and clinical outcomes were documented on a well-structured questionnaire. Results: The mean age of the patients was 39.9±3.4 years with highest number of patients who came for an ultrasound was between 38-42 years. There were more women suffering from asymptomatic gallbladderstones. The ultrasonographic evaluation showed that only 6% patients with symptomatic cholelithiasis had gallbladder wall thickening greater than 3mm. Pericholecystic fluid was also not presented in majority of the patients. Ultrasonography was positively able to identify gall stones in 97% of the asymptomatic cases Conclusion: Ultrasonography gave substantial results in almost 97% of the patients. Radiologists should have expertise in prompt diagnosis and treatment of underlying condition.